Short-chain fatty acids: key antiviral mediators of gut microbiota - Xu, Zhiqiang; Wang, Tao; Wang, Yanjin; Li, Yongfeng; Sun, Yuan; Qiu, Hua-Ji (Frontiers in Immunology, 2025)
The effects of gut microbiota on antiviral immunity have been well-documented in recent years, whereas a mechanistic understanding of microbiota-derived metabolite-related signaling pathways is still lacking. Short-chain fatty acids (SCFAs), key metabolites produced by gut bacterial microbiota via dietary fiber fermentation and amino acid metabolism, have been shown to facilitate host antiviral responses. In this review, we summarized the detailed mechanisms which could contribute to the regulation of antiviral immunity engaged and initiated by SCFAs, involving G-protein-coupled receptor (GPCR)-mediated, histone deacetylase (HDAC)-mediated, and metabolic pathways. We also discuss the implications of SCFAs for viral disease management and pandemic preparedness. This review provides novel insights into the antiviral activities of SCFAs and highlights the therapeutic potential of SCFA-producing bacteria.